Fatal poisonings in Nordic countries in 2022 among people who use drugs - Pirkko Kriikku; Hilde Marie E. Edvardsen; Gunilla Thelander; Svava Thordardottir; Charlotte Uggerhøj Andersen; Ilkka Ojanperä; Anna K. Jönsson; Joachim Frost; Simon Kjær Hermansen; Gerd J.M. Delaveris; Kirsten Wiese Simonsen (Forensic Science International: Reports)
The present study is a survey of fatal poisonings occurring in 2022 among people who use drugs (PWUD) in the Nordic countries. This is the eighth report in a series of studies on PWUD conducted about every fifth year since 1984 by a working group representing Denmark, Finland, Iceland, Norway and Sweden.Data on the number of deaths, gender, age, place of death, main intoxicant, and drugs detected in blood were recorded. National data were compared between the Nordic countries as well as with the earlier studies. The death rate (number of deaths per 100,000 inhabitants) among PWUD in 2022 was highest in Norway (8.03), followed by Iceland (7.20) and Finland (5.95), and lowest in Denmark (5.09). This rate increased in all countries compared to 2017, except in Sweden, which saw a decrease from 6.46 to 5.91. The change was only statistically significant in Norway. Most deaths occurred among men, with women accounting for 16–23 %. The median age at the time of death among PWUD was 40–43 years in Denmark, Norway and Sweden, while it was about ten years younger in Finland and Iceland (median age 33 years). Opioids were the main cause of PWUD death in all countries. The proportion of opioid deaths amounted to 73–89 % and was lowest in Denmark and highest in Iceland. New psychoactive substances (NPS) were sporadically detected in all countries but were rarely the main intoxicant. The largest diversity of NPS was detected in Finland and Sweden.